Development of a religious non-radicalism model from local churches" perspectives - Saimima, Johan R. (HTS teologiese studies, 2025)
Religious institutions often encourage religious radicalism among their adherents in a pluralistic society. Therefore, there is an urgency for a religious non-radicalism model, especially in local churches in Maluku and North Maluku, Indonesia. This study emphasises the role of local churches in maintaining the integrity of society through a model of religious non-radicalism that reflects a wise way of believing and bringing goodness to humanity. This research employs a qualitative phenomenological approach to examine religious non-radicalism based on Pancasila, Ernest Renan’s concept of living together and a theology of utilitarianism. The study engages in dialogue with social and cultural capital within the context of local churches, particularly in Maluku and North Maluku. It maps the concept of religious non-radicalism in local churches, focussing on social and cultural capital as well as understanding related to religious non-radicalism. The research then analyses empirical experiences and the implementation of teachings, regulations and programmes in local churches teachings, regulations and programmes) and developed into churches. This analysis leads to the development of a model of religious non-radicalism from the perspectives of these churches. The key finding of this research, which contributes novelty to the article, is the model of religious non-radicalism at the levels of Gereja Protestan Maluku, including Synod, Klasis [Classis] and Congregation. This model is derived from the cultures based on the perspectives of local churches. Cultural institutions such as Pela Gandong, Ain ni Ain and Saruma serve as solid foundations for the lives of the orang basudara and can be instrumental in fostering coexistence amid religious differences while rejecting violence in the name of religion in social life.Contribution: This article contributes to the development of a religious non-radicalism model from the perspective of local churches to maintain peace.